Analysis of Cardiovascular Drugs Inventory Control Using ABC-EOQ-ROP-SS Method at Jakarta Islamic Hospital - Nopiana Nopiana; Atik Nurwahyuni (Universitas Muhammadiyah Yogyakarta, 2020)
Cardiovascular disease was still a global threat and give a major role as the number one cause of death in the world. Patients with CVDs should take the medication regularly so that the availability of these drugs in health facilities must be maintained. And then, Cardiovascular drugs were the highest usage costs during 2019, which is around Rp. 6,924,415,718.20 (22.62%) so that it requires special attention to control the inventory. The object of this research was to determine the implementation of cardiovascular drug inventory control using ABC-EOQ-ROP-SS method to minimize the stock inventory, while maintaining the service level. This research used a non-experimental comparative method with retrospective cardiovascular drug data collection in 2019. Data obtained through the documentation of the Pharmacy Installation section and the logistics section. The data were analyzed to determine the cost efficiency of cardiovascular drugs using the ABC-EOQ-ROP-SS method compared to actual data for drug orders in January-December 2019 .The results of ABC-EOQ-ROP-SS methods in controlling cardiovascular drugs can be implemented by the Jakarta Islamic Hospital to minimize stock inventory, while maintaining the service level and can increase the total cost efficiency up to 17,91% of the actual order .